A Cost-of-Illness Study of Patients with HIV/AIDS in Bogotá, Colombia (2017)
Background In 2014, 0.3% of the total population in Colombia was living with HIV/AIDS. The data currently available regarding the costs of these patients are very limited. Objectives To estimate the societal costs of patients with HIV/AIDS in Bogotá, Colombia. Methods This study is a quantitative, cross-sectional cost-of-illness study. Costs were assessed with a prevalence-based, bottom-up approach. The data of 124 patients were collected from their medical records in a Bogotá hospital and a questionnaire was developed to measure other health care costs, as well as patient and family costs. Subgroup analyses were performed according to sex, age, Centers for Disease Control and Prevention classification, and CD4 count (cluster of differentiation 4). Results The mean annual cost per patient with HIV/AIDS was estimated at $11,505 ± 18,658 (2014 US dollars). The larger part was attributable to drug costs (a mean annual cost of $8,616, 75% of the total), whereas productivity costs represented a mean annual cost of $1,044 (10%). Total costs per patient were estimated for a CD4 count of 500 or more, 200 to 499, and less than 200 cells/µl at $13,116, $9,077, and $10,741, respectively (all values in 2014 US dollars). Conclusions HIV/AIDS represents a high societal burden in Colombia. In comparison with the gross domestic product per capita of $7,904 in 2014, the mean annual cost per patient with HIV/AIDS was 40% higher, estimated at $11,505. The largest part of the HIV/AIDS costs was attributed to drugs, followed by productivity costs. Using extrapolation, the total cost of HIV/AIDS for the Colombian society would be $1.431 billion. © 2017